Analisis Pendapatan dan Kontribusi Pemburu Madu Hutan terhadap Rumah Tangga Petani di Desa Lantung Kecamatan Lantung Kabupaten Sumbawa - Patima; Nurwahidah, Siti; Wijayanti, Nila (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
This research analyzes the feasibility of income for forest honey hunters in Lantung Village, Lantung District, and analyzes how much the business of hunting forest honey bees contributes to the income of farmers in Lantung Village, Lantung District. This research was carried out in Lantung Village, Lantung District. The research was conducted in May-July 2023. The type of data used is quantitative data and the data sources are primary data and secondary data. The sampling method was carried out by census with a total sample of 36 hunters. The results of the research show that (1) The income from hunting for forest honey obtained by farmers in Lantung Village, Lantung District is IDR. 25,633,000/year, (2) The forest honey hunting business in Lantung Village, Lantung District is feasible to run, seen from the B/C ratio = 5.7> 1, (3) The contribution of the forest honey hunting business in Lantung Village, Lantung District to the total income of farming households is 63%.